Influence of academic training in the conception of journalism as a profession in Ecuador - Odriozola Chéné, Javier (2016)
Currently, the professionalization of journalistic practice is being promoted from government areas of the Republic of Ecuador through the Communication Law. The goal of this paper is to identify the influence of academic education of the Ecuadorian journalists, when conceiving the performance of journalistic practice. To do this, forty interviews were conducted, semi-structured, to Ecuadorians active journalists on the four types of media (newspapers, television, radio and internet). The results shows that journalists detect a rupture between what they learned in university classrooms versus the professional practice. Ecuadorian professionals relate this break with academic programs too theoretical as other overly technical or general.